Integrating Ethnomathematics in Geometry Learning to Enhance Primary Students’ Numeracy Skills: A Systematic Literature Review - Zainovi, Putri Sarah; Mariana, Neni; Istiq'faroh, Nurul; Wiryanto, Wiryanto; Muhimmah, Hitta Alfi (Papanda Publisher, 2025)
This study presents a systematic literature review aiming to explore the integration of ethnomathematics in the teaching of plane geometry as a means to enhance numeracy skills among primary school students. Ethnomathematics, which connects mathematical concepts with local cultural practices, offers a contextual and meaningful learning experience that aligns with students’ everyday lives. The review was conducted by analyzing ten peer-reviewed studies published between 2021 and 2024, sourced from credible academic databases such as Google Scholar, DOAJ, ERIC, and Garuda. The findings indicate that embedding cultural elements into geometry instruction—such as traditional motifs, crafts, and architecture—not only improves students’ conceptual understanding but also promotes critical thinking, collaboration, and motivation to learn. Instructional tools developed using ethnomathematical approaches, including modules, multimedia, animated videos, and augmented reality, were reported to be valid, practical, and effective in classroom implementation. Moreover, this culturally responsive pedagogy supports the development of a more inclusive and identity-affirming mathematics education. The review highlights the pedagogical value of ethnomathematics and recommends its wider adoption in mathematics curricula, teacher training, and educational policy. Future research should focus on experimental designs and cross-cultural implementations to further validate the long-term impact of ethnomathematics on student learning outcomes.